Diferenças de remuneraç\~ao entre trabalhadores sndicalizados e n\~ao sindicalizados: Evidências sobre o mercado de trabalho brasileiro - André Gambier Campos; Ana Carolina Moura (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This paper presents new empirical evidence about the wage gap between union and nonunion workers in Brazil. In principle, due to the rules governing union organization/mobilization, no one should rationally expect such gap. But, as this paper reveals, there is empirical evidence of its existence in the labour market. Furthermore, this wage gap may increase in the future, depending on how the labour reform conducted through the Bill no 6.787/2016 (under discussion in the Parliament) may be implemented.
Keywords: J00; J31; J51; 330; unions; collective bargaining; wages